Concurrent Extramedullary Hematopoiesis and Pseudometastatic Hypervascular Lesions Masquerading as Metastases in Liver in a Case of Neuroblastoma - Taori, Abhijeet; Shenouda, Nazih; Demellawy, Dina El; Putnins, Rita (Indian Journal of Radiology and Imaging, 2021)
Neuroblastoma is a common embryonic tumor presenting in childhood. Improving treatment protocols which include a combination of chemotherapy, surgical resection, hematopoietic stem cell rescue, and radiation therapy have tremendously improved outcomes. Childhood survivors are at risk of developing lesions which may mimic metastases. It is essential to accurately diagnose these due to its prognostic implications.
Keywords: extramedullary hematopoiesis; neuroblastoma; pseudometastatic hypervascular lesions